087 Endovascular clot retrieval (ECR) in the elderly. For better or worse in the real world?. (29th July 2019) - Jankelowitz, Stacey K; Tastula, Kylie; Mitchell, Nicola; Tang, Patrick; Ang, Tim; Brunacci, David; Parker, Geoffrey; Winters, Stephen; Wong, Johnny; Allen, Rodney; Worthington, John
Abstract : Introduction: Across multicentre trials ECR is safe and effective in octogenarians. Despite RCT evidence elderly patients may be denied ECR due to perceived poor risk-benefit. We examine impact of age on ECR outcomes and outcomes in transcatheter aortic valve implantation (TAVI) cases (where stroke risk is high), in a real world setting. Methods: We analysed 311 consecutive ECR cases between 2016 and 2019 in 10 year age bands for ECR outcomes including 90 day mRS and mortality. Impact of premorbid function (mRS), NIHSS, recorded co-morbidities, and aetiology was assessed. TAVI case outcomes were examined. Results: Thirty one percent of ECR outcome cases were over 79 years of age; 90 day mortality was 34%; 25% had a 90 day mRS 0–2. Early NIHSS improvement was 5. Ninety-day mortality and mRS 0–2 for 10–19 (n=3), 20–29 (n=2), 30–39 (n=4), 40–49 (n=23), 50–59 (n=27), 60–69 (n=69), 70–79 (n=84), 80–89 (n=62) and 90–99 (n=11) years were 0 and 100%, 0 and 100%, 33 and 67%, 4 and 78%, 15 and 52%, 13 and 49%, 17 and 33%, 24 and 2% and 55 and 18%, respectively. There was 9% lost to follow-up. Six TAVI cases had a NIHSS of 8–20 and pre-morbid mRS<3, four with mRS 0. Mean 24 hour NIHSS improvement was 8. Conclusion: Without age exclusions older patients had worse unadjusted outcomes. However, patients over 79 years had clinically important early improvement in NIHSS score and ninety day outcomes were comparable to favourable RCT data and TAVI patients also had early improvement.